Studi Fenomenologi : Pengalaman Pasien Prioritas Paling Rendah Pada Klasifikasi Triage Di IGD RSUD Dr. Iskak Tulungagung - Elfi Quyumi Rahmawati; Retty Ratnawati; Fransiska Imavike (Akademi Keperawatan Dharma Husada Kediri, 2013)
While many patients present simultaneously, triage is an important function in the ER in sorting patients based on severity. Patients with lower priority will wait longer for assessment and treatment. The purpose of this study was to explore the experience of patient at the lowest priority in the emergency department. Methods of this research conducted with a qualitative approach appropriate design philosophy of Heidegger's interpretive Obtained from this purposive sampling technique 5 participants. Analysis of the data from this study uses an interpretive approach to the analysis of Van Manen found the core theme based comfortable for a patient in the ER. Experience this convenience in the form of five primary themes of experience in handling by workers, delivery of information by officers, ethics officers, environment and procedural in the ER. Based on these results it is recommended for health care workers in the emergency room to further improve communication, information, and education on patient lowest priority, or the formation of a special team that is responsible for communication problems. Key words : patients with lower priority, experience, qualitative